Students' evaluation of oral health education ava teaching module - Amy, Liew Kia Cheen; Rahimah Abdul Kadir,; Nurul Asyikin Yahya,; Haslina Rani, (Penerbit Universiti Kebangsaan Malaysia, 2013)
Audio-visual aids were widely used in raising dental awareness of the public. Faculty of Dentistry, Universiti Kebangsaan Malaysia introduced a 20-hour ‘Oral Health Education – Audio-Visual Aids’ (OHE-AVA) module requiring students to plan, produce, use and evaluate OHE-AVA materials for individual patients and in the community. Course evaluation was carried out at the end of the module to assess fourth-year dental students’ perception on the conduct and usefulness of ‘OHE-AVA’ as a learning module in the undergraduate curriculum. Self-administered questionnaires with five-point Likert Scales on skills development and teaching-learning environment were disseminated to two Year Four cohorts. A total of 123 completed questionnaires were returned. In ‘Development of Abilities’, most students agreed on improvement of critical thinking, creative thinking, self-managed learning, adaptability, problem solving, communication skills and computer literacy. In contrast, the responses for interpersonal skills and group work development were poorer (1.6% and 4.9% disagreement). Responses were positive for ‘Teaching and Learning Environment’, except for Feedback to Assist Learning (21.1% and 22.8% undecided). Disagreement was reported higher in the two statements on Workload, scoring 7.3% and 4.9% respectively. Nevertheless, most students observed the relevance of the module to the Dental Public Health course (86.9%), to other modules (86.8%) and to the entire dental programme (89.4%). Of the 123 students, 87.8% agreed that learning objectives were stated beforehand and 84.5% agreed that the course objectives were met. In conclusion, the OHE-AVA module was positively rated by students. Nonetheless, concerns regarding students’ interaction, assessment and workload could be improved.